Mixed-race in the US and UK : comparing the past, present, and future - Sims, Jennifer Patrice; Njaka, Chinelo L. (Critical mixed race studies., 2019)
Contributing to an emerging literature on mixed-race people in the United States and United Kingdom, this book draws on racial formation theory and the performativity (i.e. "doing") of race to explore the social construction of mixedness on both sides of the Atlantic Ocean. In addition to macro- and micro-level theoretical frameworks, the authors use comparative and relational analytical approaches to reveal similarities and differences between the two nations, explaining them in terms of both common historical roots as well as ongoing contemporary interrelationships.Focusing on the census, racial identity, civil society, and everyday experiences at the intersection of race, gender, class, and sexuality, Mixed-Race in the US and UK: Comparing the Past, Present, and Future offers academics and students an intriguing look into how mixed-race is constructed and experienced within these two nations. A final in-depth discussion on the authors' research methodologies makes the book a useful resource on the processes, challenges, and benefits of conducting qualitative research in two nations.